Non-invasive measurement of adrenocortical and gonadal activity in male and female guinea pigs (Cavia aperea f. porcellus) - Bauer, Barbara; Palme, Rupert; Machatschke, Ivo H.; Dittami, John; Huber, Susanne (General and comparative endocrinology, 2008)
Taking blood samples is a common method in biomedical and biological research using guinea pigs. However, most blood sampling techniques are complicated and highly invasive and may therefore not be appropriate for certain research topics concerning stress and reproduction. Thus, a non-invasive method to measure steroid hormones is critically needed. The aim of this study was the biological validation of corresponding enzyme immunoassays for the measurement of fecal cortisol, progesterone, estrogen, and testosterone metabolites in guinea pigs. We examined the effect of subcutaneous injections of ACTH or saline on fecal cortisol metabolites to investigate the suitability of fecal samples to monitor adrenocortical activity. Furthermore, we investigated whether fecal sex steroid metabolites accurately reflected endocrine changes observed in plasma samples during female estrous cycles and male puberty, respectively. In addition, we compared fecal testosterone metabolites of intact males, castrated males, and females to investigate the reliability of fecal samples in discriminating gonadal status of males. Concentrations of fecal cortisol metabolites were significantly increased following ACTH challenge, indicating that adrenocortical activity can be monitored via fecal samples. Secondly, in females, plasma and fecal gonadal steroids were significantly correlated in most subjects. The assay for testosterone metabolites, on the other hand, could not clearly discriminate between test groups. From these findings we conclude that fecal samples can be used for the non-invasive assessment of adrenocortical and female reproductive status in guinea pigs. Testosterone metabolism seems to be more complex and further investigations are needed to establish a more suitable assay.